OMQ-14 and ECLiPS questionnaires: Potential adjuncts in the assessment of otitis media with effusion?. (August 2019) - Barry, Johanna G.; Freigang, Claudia; Birchall, John P.; Daniel, Mat
Abstract: Objective: To assess the capacity of two parental report questionnaires, OMQ-14 and ECLiPS, to support clinical-decision making in children affected by Otitis Media with Effusion (OME). Design: OMQ-14 and ECLiPS were administered twice to 90 children aged 2–12 years, three months apart, or 3 months after surgery to insert ventilation tubes (VT). Children were subdivided according to clinical diagnosis into VT (n = 25) and Active Observation (AO; n = 20), and compared with healthy control children (n = 45). Data were analyzed at group level using repeated measures ANOVA, and at individual level using Receiver Operator Characteristics (ROC) curves and confusion matrices. Results: Both OMQ-14 and ECLiPS were sensitive to the presence of OME, and also to improvements in hearing post-surgery. Both were also good at classifying children into their clinically-established diagnostic groups based on score cut-offs determined using Receiver Operator Characteristics (ROC) curves. However, outputs from confusion matrices suggest only around 50% of children after VTs would be indistinguishable from controls following VT surgery. Differences were observed in which children were identified as still having problems according to the questionnaires. OMQ-14 is more sensitive to disease-related hearing loss, while the ECLiPS is more sensitive to developmental difficulties. Conclusions: Despite being developed with different aims in mind, the OMQ-14 and ECLiPS were similarly sensitive both to symptoms of disease-related hearing difficulty and also to treatment-related improvements in hearing. A significant number of VT children continue to have poor OMQ-14 and ECLiPS scores relative to control children. ECLiPS scores do not always change in a way that hearing improvements would predict, suggesting the ECLiPS is sensitive to wider developmental difficulties. Parental report in the form of narrow or broad-based questionnaires may complement history-taking and audiometry to enhance the quality of discussion between carers and clinicians about OME management.